Incidence of post-surgical complications in patients undergoing total knee arthroplasty: a prospective study with 122 patients - Pavão, Douglas Mello; Titonelli, Victor Elias; Barroso, Murilo; Rocha Faria, José Leonardo; Mozella, Alan de Paula; Cobra, Hugo; Pires e Albuquerque , Rodrigo Satamine (Brazilian Journal of Case Reports, 2022)
Total knee arthroplasty (TKA) represents an effective therapeutic option for the treatment of advanced cases of knee osteoarthritis. Although considered safe, monitoring in the intensive care unit (ICU) reduces the chance of early fatal complications, and for this reason, many specialized treatment centers refer their patients to the ICU in the immediate postoperative period. We prospectively evaluated 122 patients monitored in the ICU for 24 hours after TKA to assess the profile of patients who had complications and to determine incidence of post-surgical complications. The most common complications were hypotension (6 cases; 28.57%), delirium (3 cases; 14.29%), hypovolemia (2 cases; 9.52%), hypoxemia (2 cases; 9.52%) and anemia (2 cases; 9.52%) The factor that showed a statistically significant positive correlation with complications was age over 70 years (p=0.015). We concluded that here was an association between the patient's age and the presence of post-surgical complication, and it was identified that the most common postoperative complication in the first 24 hours in the ICU was hypotension. Factors such as sex, diabetes, SAH, obesity and smoking are still conflicting and need more investigation.